Sibling Species Composition and Susceptibility Status of Anopheles gambiae s.l. to Insecticides Used for Indoor Residual Spraying in Eastern Uganda - Julius Iga; Stephen Ochaya; Richard Echodu; Elizabeth A. Opiyo; Alex K. Musiime; Angella Nakamaanya; Geoffrey M. Malinga (Journal of Parasitology Research)
Background. Malaria remains one of the most critical disease causing morbidity and mortality in Uganda. Indoor residual spraying (IRS) and the use of insecticide-treated bed nets are currently the predominant malaria vector control interventions. However, the emergence and spread of insecticide resistance among malaria vectors threaten the continued effectiveness of these interventions to control the disease, particularly in high transmission areas. To inform decisions on vector control, the current study evaluated the Anopheles malaria vector species and their susceptibility levels to 0.1% bendiocarb and 0.25% pirimiphos-methyl insecticides used in IRS intervention program in Namutumba district, Eastern Uganda. Methods.Anopheles larvae were collected between March and May 2017 from different breeding sites in the parishes of Nsinze and Nawaikona in Nsinze sub-county and reared to adults to assess the susceptibility status of populations in the study area. Mosquitoes were identified using morphological keys and species-specific polymerase chain reaction (PCR) assays. Susceptibility tests were conducted on 2- to 5-day-old non-blood-fed adult female Anopheles that emerged using insecticide-impregnated papers with 0.1% bendiocarb and 0.25% pirimiphos-methyl following standard World Health Organization (WHO) insecticide susceptibility bioassays. A Log-probit regression model was used to derive the knock-down rates for 50% and 95% of exposed mosquitoes. Results. A total of 700 mosquito larvae were collected from different breeding sites. Morphological identification showed that 500 individuals that emerged belonged to Anopheles gambiae sensu lato (s.l.), the main malaria vector. The PCR results showed that the dominant sibling species under the A. gambiae complex was Anopheles arabiensis 99.5% (395/397). WHO bioassay tests revealed that the population of mosquitoes exhibited high levels of susceptibility (24-hour post-exposure mortality 98–100%) to both insecticides tested. The median knock-down time, KDT50, ranged from 6.6 to 81.4 minutes, while the KDT95 ranged from 21.6 to 118.9 minutes for 0.25% pirimiphos-methyl. The KDT50 for 0.1% bendiocarb ranged from 2.8 to 62.9 minutes, whereas the KDT95 ranged from 36.0 to 88.5 minutes. Conclusions. These findings indicate that bendiocarb and pirimiphos-methyl are still effective against the major malaria vector, A. arabiensis in Nsinze sub-county, Namutumba district, Uganda and can be effectively used for IRS. The study has provided baseline information on the insecticide susceptibility status on malaria vectors in the study area. However, routine continuous monitoring program of insecticide susceptibility and malaria vector composition is required so as to guide future decisions on insecticide use for IRS intervention toward malaria elimination and to track future changes in vector population.